Genetic analysis of drought tolerance in adapted X exotic crosses of maize inbred lines under managed stress conditions - Adebayo, M.A.; Menkir, A.; Blay, E.; Gracen, V.E.; Danquah, E.Y.; Hearne, S. (Springer, 2014)
Abstract Introduced maize (Zea mays L.) germplasmcan serve as sources of favorable alleles toenhance performance in new maize varieties andhybrids under drought stress conditions. In the presentstudy, the combining abilities of 12 exotic maizeinbred lines from CIMMYT and 12 adapted maizeinbred lines from IITA were studied for grain yield andother traits under controlled drought stress. The inbredlines from each institution were separated into groupsusing SSR-based genetic diversity and were intercrossedusing a factorial mating scheme to generate 96hybrids. These hybrids were evaluated under bothcontrolled drought stress and well-watered conditionsat Ikenne in Nigeria in 2010 and 2011. Average meanyields of hybrids under drought stress represented23 % of the average yield of hybrids under fullirrigation. General combining ability (GCA) effectsaccounted for 49–85 % of the observed variation forseveral traits recorded under both well-watered anddrought stress conditions. Specific combining abilityeffects for grain yield, though positive in most hybrids,were not significant under drought stress conditions.All the twelve exotic and nine adapted lines hadpositive GCA effects (female, male, or both) for grainyield under either drought stress or full irrigation, orboth environments. EXL03 and EXL15 that hadpositive and significant female and male GCA effectsfor grain yield under both environments can be used toimprove their adapted counterparts for grain yield anddrought tolerance. Normalized difference vegetationindex had weak but significant correlation with grainyield.